The complete Big Nate.Volume 2 book 2 Volume 2 book 2 - Peirce, Lincoln; Peirce, Lincoln; hoopla digital (United States : Andrews McMeel, 2015)
The Complete Big Nate collects every daily and Sunday cartoon ever syndicated. Presented in a numbered series of e-books, each containing one year's worth of strips, this is a goldmine for all Big Nate fans to see many cartoons that have never been published in books. Aspiring cartoonist Nate Wright is the star of Big Nate. As a popular middle-grade book character, Nate is 11 years old, four-and-a-half feet tall, and the all-time record holder for detentions in school history. He's a self-described genius and sixth grade Renaissance Man. Nate, who lives with his dad and older sister, has a habit of annoying his family, friends, and teachers with his sarcasm.
Rated E
Mode of access: World Wide Web.
Keywords: Boys -- Conduct of life -- Comic books, strips, etc; Middle schools -- Comic books, strips, etc; Electronic books; Graphic novels; Comic books, strips, etc